A Comparative In Silico Study of the Antioxidant Defense Gene Repertoire of Distinct Lifestyle Trypanosomatid Species. (January 2016) - Beltrame-Botelho, Ingrid Thaís; Talavera-López, Carlos; Andersson, Björn; Grisard, Edmundo Carlos; Stoco, Patricia Hermes
Kinetoplastids are an ancestral group of protists that contains free-living species and parasites with distinct mechanisms in response to stress. Here, we compared genes involved in antioxidant defense (AD), proposing an evolution model among trypanosomatids. All genes were identified in Bodo saltans, suggesting that AD mechanisms have evolved prior to adaptation for parasitic lifestyles. While most of the monoxenous and dixenous parasites revealed minor differences from B. saltans, the endosymbiont-bearing species have an increased number of genes. The absence of these genes was mainly observed in the extracellular parasites of the genera Phytomonas and Trypanosoma. In trypanosomes, a distinction was observed between stercorarian and salivarian parasites, except for Trypanosoma rangeli. Our analyses indicate that the variability of AD among trypanosomatids at the genomic level is not solely due to the geographical isolation, being mainly related to specific adaptations of their distinct biological cycles within insect vectors and to a parasitism of a wide range of hosts.